Problematika Perkawinan Akibat Perselingkuhan Yang Menimbulkan Perceraian (Examinasi Putusan Nomor 311/ Pdt.G/ 2020/ Pn Kpg) - Fin Tae, Mericiana Yulita; Tamelab, Vinsensius; Rade, Stefanus Don (Media Hukum Indonesia (MHI), 2024)
Marriage is the beginning of life together between a man and woman as husband and wife, while divorce is the end of life together between husband and wife. Marriage is a very fundamental institution in society, so it has legal protection. The law always defends, prioritizes and favors the validity of marriage. Consequently, in cases of doubt regarding its validity, the law protects and maintains the validity of marriage, until proven otherwise after various investigations, including the issue of infidelity. So, constant disputes and quarrels can be the reason for the dissolution of a marriage, "between husband and wife there are constant disputes and quarrels and there is no hope of living in harmony in the household again" (Article 19 letter (f) Government Regulation Number 9 in 1975).